Study on the Social Service Function and Practical Path of Guangdong Vocational Education City in Qingyuan City's “One Hundred Million Project” - Li, Yingmei; Zhang, Tongyu; Chen, Zhenhao; Wu, Gan; Zhong, Feng; He, Dongjin (International Journal of Global Economics and Management, 2024)
The purpose of this paper is to study the social service function and practice path of Guangdong Vocational Education City (VEC) in the “One Million Project” of Qingyuan City. By means of literature review and case study analysis, it explores the practice and effectiveness of the VTC in the sharing of educational resources, integration of industry and education, talent cultivation, scientific research and innovation, cultural inheritance and social governance, etc. The study finds that the VTC has played an important role in promoting the social service function of Qingyuan City in the “One Million Project”. The study finds that VTCs have played an important role in promoting local economic development, facilitating industrial upgrading, and upgrading the quality of education, but they also face challenges in resource allocation, cooperation mechanisms, and talent cultivation models. This paper puts forward a series of countermeasures and suggestions, including strengthening policy support, innovating cooperation mechanism, and reforming talent cultivation mode, in order to enhance the social service function of VTC. At the same time, this paper also points out the limitations of the study and makes suggestions for future research directions.